Analisis Pengaruh Kapasitor Bank Terhadap Besaran Listrik di Gedung World Trade Centre Jakarta - Muhammad Rivaldi Agustian; Edy Sumarno; Kartika Sekarsari; Sunardi Sunardi (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
High-rise buildings such as the World Trade Center Jakarta generally have high inductive electrical loads, so that their reactive power consumption is large and the power factor decreases below the SPLN standard (≤0.85), resulting in increased power losses and operational costs. This study aims to measure the power factor value before and after repairing the detuned reactor and capacitor on the capacitor bank panel, compare the results of field measurements with ETAP simulations, and assess the feasibility of the installed capacitor bank and determine the difference in the results of the ETAP simulation between measurements and load calculations on the World Trade Center building. The methods used include literature review, field observations on the LVMDP panel, MCC and capacitor bank, discussions with supervisors, data collection of current, voltage, kW, kVAR, kVA and cos φ using Lovato DCRG8 and ampere clamp, and load simulation using ETAP software. The results show that the cosφ value increased from 0.70 to 0.95 (an increase of 35.71%), the compensated reactive power reached 204 kVAR (Lovato), 282.6 kVAR (tang ampere), and 415 kVAR (ETAP simulation), with a power factor or cosφ = 0.95. In conclusion, the replacement of detuned reactors and capacitors effectively improves the power factor in the WTC Jakarta Building, reduces reactive loads, and the ETAP simulation results are consistent with field measurements, so that the capacitor bank installed in the WTC building is declared effective in reducing reactive currents, thereby reducing kVAR, kVA loads and improving the efficiency of the electrical system distribution for better energy management